Betwixt and between: workplace perspectives on work reintegration in the eldercare sector in Denmark. (October 2015) - Ladekjær Larsen, Eva; Labriola, Merete; Vinther Nielsen, Claus; Schultz Petersen, Kirsten
Abstract Purpose: Contemporary return-to-work (RTW) policies in Denmark and other welfare nations recommend employees on long-term sick leave, due to physical or mental health problems, to RTW gradually. Factors that influence the process of work reintegration (WR) is well documented, however, co-workers experiences of this process are a rather new research topic. Moreover, in the context of the present research, no studies have so far explored the workplace as an arena for social interaction. The aim of this study was to explore co-workers' experiences of the reintegration process and how these experiences are related to social positions at the workplace. Methods: Ethnographic fieldwork was conducted at two nursing homes that were in a process WR after long-term sick leave. The data consist of field notes, policy documents, individual interviews, and focus group interviews. Data were organized by use of NVivo. A theoretical framework was adopted which enabled us to approach and interpret the reintegration process as one that changed the social position of the returning employee. Results: The dataset demonstrates how the returnee is in a state of being betwixt and between the social positions of a co-worker and a non-co-worker. This is illustrated in three cases which show that this state prevents the returnee from taking on the role as a co-worker, excludes the returnee from the workplace, and creates uncertainty for all workplace actors. Conclusion: The study highlighted that WR creates a social position for the returnee that complicates the working routine and causes uncertainty in social interactions. Implications for Rehabilitation Work reintegration (WR) after long-term sick leave is commonly characterized by reduced working hours and modified working tasks. The WR process influences the whole work place including co-workers' everyday working life and complicates work situations where work tasks and roles are negotiated between the returning worker and co-workers. Future WR policies and guidelines could benefit from integrating co-workers' perspective to ensure that the returning worker is not socially excluded as well as ensuring that co-workers are not overburdened in the process.